Digital Extroversion: The Role of Perceived Anonymity, Online Comfort, and Digital Cue Adaptation Among Senior High School Students - Kristen Yeliz P. Alojipan; Maybelle Allyson Miranda; Allyssa Nicole S. Ong; Jodi Maxine F. Picazo; Anjeanette A. Ramirez; Myla M. Arcinas (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study was geared towards finding out the effect of perceived anonymity, online comfort, and digital cue adaptation on the extent of digital extroversion of grade 12 students of a selected University in Metro Manila (n=114). The research used in this study was explanatory in a quantitative paradigm. The convenience sampling method was used in selecting the target population of this study. The data were collected through an online survey and analysed by descriptive statistics, Spearman’s rho and multiple linear regression. The participants used social media or integrated it in their lives “Very High” (Md = 5.00) as shown in descriptive statistics. They had a “High” average rating of digital cue adaptation (Md = 4.00), “Low” average rating of perceived anonymity (Md = 2.50), “Moderate” average rating of online comfort (Md = 3.25) and “Moderate” average rating of digital extroversion (Md = 3.25). A correlational analysis was used to see the correlations between the variables, and the analysis showed that the digital extroversion variable was positively correlated with the variable Online Comfort (ρ = .426, p < .001). The relationship between digital extroversion and digital cue adaptation was found to be “Weak Positive” (ρ = .176, p = .062). Online Comfort seemed to explain the 16.7% of variance in the unique manner (p < .001, β = 0.343). The results of this study extended the understanding of students' online behaviors with evidence that challenges the main tenet of the online disinhibition hypothesis.